Functional radical cervical dissection for differentiated thyroid cancer: the experience of a single center - Adrian Tulin; Lucian Alecu; Catalina Poiana; Luminita Tomescu; Iulian Slavu; Raluca Tulin; Silviu Pituru; Cristina Orlov; Radu Jecan; Cristian Balalau; Anca Pantea Stoian; Razvan Hainarosie; et al. (Journal of Mind and Medical Sciences)
There is ongoing debate regarding the role of neck dissection in differentiated thyroid cancer, about its usefulness in elective settings, and the increased costs regarding morbidity and operative time. This retrospective study aimed to determine the rate of metastases in cervical lymph nodes, to examine the morbidity of this surgery, and to assess whether a pattern of distribution of tumor cells concerning neck lymphatic compartments exists. The most frequent type of cancer to metastasize was papillary cancer, the majority of patients were young with a median of 30 years, predominantly females. Differentiated thyroid cancer frequently metastasizes to the central and lateral compartments of the neck. The morbidity is minimal in a high-volume center. Radical neck dissection is safe and feasible in selected patients with confirmed invaded or enlarged lymph nodes due to differentiated thyroid cancer, and postoperative complications are minimal if the anatomy is correctly identified and the cases strictly selected.